2001
DOI: 10.1046/j.0014-2956.2001.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, and cDNA cloning of a novel soluble saxitoxin and tetrodotoxin binding protein from plasma of the puffer fish, Fugu pardalis

Abstract: Some species of puffer fish have been reported to possess both of tetrodotoxin and saxitoxin, which share one binding site on sodium channels. We purified a novel soluble glycoprotein that binds to these toxins from plasma of the puffer fish, Fugu pardalis, and named puffer fish saxitoxin and tetrodotoxin binding protein (PSTBP). PSTBP possessed a binding capacity of 10.6 ± 0.97 nmol·mg−1 protein and a Kd of 14.6 ± 0.33 nm for [3H]saxitoxin in equilibrium binding assays. [3H]Saxitoxin (10 nm) binding to PSTBPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 35 publications
(53 reference statements)
2
76
0
Order By: Relevance
“…TTX/PST-binding proteins have been isolated from the blood plasma of marine pufferfish (Matsui et al, 2000;Yotsu-Yamashita et al, 2001), and may be involved in the transportation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…TTX/PST-binding proteins have been isolated from the blood plasma of marine pufferfish (Matsui et al, 2000;Yotsu-Yamashita et al, 2001), and may be involved in the transportation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…4) Two cDNAs encoding distinct PSTBP isoforms (PSTBP1 and PSTBP2, with 93% amino acid sequence identity) were cloned and sequenced. 4) Although it has been suggested that PSTBPs appear as non-covalently linked dimers of a single subunit, 4) it is unknown whether PSTBPs form homodimers or heterodimers with both isoforms or either one (PSTBP1 or PSTBP2). Western blot analysis using IgG antibody against recombinant PSTBP1 suggested that a PSTBP homolog of 124 kDa (as estimated by SDS-PAGE) is present in the plasma of wild T. rubripes.…”
Section: Abstract: Takifugu Rubripes; Tetrodotoxin; Toxinbinding Promentioning
confidence: 99%
“…The pufferfish Fugu pardalis possesses yet another STX binding protein but unlike saxiphilin it can also bind TTX and its sequence was unrelated to the Na channel or bullfrog saxiphilin (Yotsu-Yamashita et al 2001;Yotsu-Yamashita et al 2002). Similar TTX binding proteins have been observed in horseshoe crabs (Ho et al 1994) and malacostracan crustacea (Nagashima et al 2002).…”
Section: Toxin Resistancementioning
confidence: 58%
“…Temperature may affect the potency of TTX and STX circulating in the blood of certain ectothermic animals which come into contact with these guanidinium toxins. Besides prey, predators which ingest toxic prey may be more sensitive at lower temperatures (Yotsu-Yamashita et al 2001). …”
Section: Temperaturementioning
confidence: 99%